Total thyroidectomy: conventional suture ligation technique versus sutureless techniques - Ali, Mahmoud N. M.; Aldardeer, Ahmed Abdelkahaar; Ali, Ayman M. A.; Radwan, Alaa A. (International Surgery Journal, 2019)
Background: Since the introduction of successful thyroidectomy no change occurred in the technique but with the innovation of sutureless surgery, sutureless thyroidectomy becomes a competitor for the conventional technique. In this study we tried to analyze the outcomes of each. Methods: This was a prospective cross armed uncontrolled randomized study included 65 patients suffering from non-malignant goiter who underwent total thyroidectomy, admitted to Sohag University Hospital from September 2017 to October 2018. Patients were randomly allocated into two groups; Group (S) managed with sutureless thyroidectomy, and Group (C) managed with conventional knot tying technique. The data of the patients were gathered and analyzed considering the operative and post-operative outcomes. All patients were followed-up for 6 -12 months. Results: We found a significantly shorter operative time (p=0.001), also the amount of intra-operative blood loss was highly significant less in Group S (p=0.001). There was higher incidence of post-operative pain in Group C (p<0.001), post-operative drainage volume was highly significantly less in Group S (p=0.001). Regarding post-operative complications; the incidence of recurrent laryngeal nerve paralysis (RLNP) was insignificant between both groups (p=0.38), in the same time the incidence post-operative transient hypocalcaemia was significantly more in Group C (P=0.025). The overall post-operative complication rate was significantly more in Group C (p=0.002). The duration of hospital stay was highly significant shorter in Group S (p=0.0001). Conclusions: The use of Harmonic FOCUS® is beneficial for both patient and surgeon; it is efficient and a trustable safe substitute to the conventional knot tying technique.